The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.homp.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A patient reported outcome measure in homeopathic clinical practice for long-term conditions

Abstract: The MYMOP2 results add to a growing body of observational data which demonstrates that when patients with long term conditions come under homeopathic care their presenting symptoms and wellbeing often improve. Offering a low cost high impact intervention to extend the range of choice to patients and to support self-care could be an important part of the NHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Using measures that assess general changes, which can be useful when comparing cases across different types of disease conditions, may also be considered. Examples of general outcome measures typically used for case research could be the intensity of symptoms on a numeric or visual rating scale, 10 the Measure Yourself Medical Outcome Profile (MYMOP), [11][12][13] and Outcome Related to Impact on Daily Living (ORIDL) (formerly known as the Glasgow Homeopathic Hospital Outcome Scale). 14,15 Consideration might also be given to using Goal Attainment Scaling (GAS), 16 which is an instrument used mainly in psychotherapy to check the achievement of individually defined therapeutic goals.…”
Section: Discussionmentioning
confidence: 99%
“…Using measures that assess general changes, which can be useful when comparing cases across different types of disease conditions, may also be considered. Examples of general outcome measures typically used for case research could be the intensity of symptoms on a numeric or visual rating scale, 10 the Measure Yourself Medical Outcome Profile (MYMOP), [11][12][13] and Outcome Related to Impact on Daily Living (ORIDL) (formerly known as the Glasgow Homeopathic Hospital Outcome Scale). 14,15 Consideration might also be given to using Goal Attainment Scaling (GAS), 16 which is an instrument used mainly in psychotherapy to check the achievement of individually defined therapeutic goals.…”
Section: Discussionmentioning
confidence: 99%
“…15 MYMOP-2 scale is routinely used in studies of long-term conditions. 22,23 In this study, patients were asked to volunteer the most troublesome symptom associated with their condition, a problem related to activity and their overall well-being on a seven-point numerical rating scale. It was found that each and every patient shown improvement in all three domains and the improvements were statistically significant after 6 weeks of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…52 The GRACE checklist is designed to guide the assessment of observational studies of comparative effectiveness in terms of their quality and usefulness for decision-making. 12,13 the Glasgow Homeopathic Hospital Outcome Scale (GHHOS), 42 the Measure Yourself Medical Outcome Profile (MYMOP), [43][44][45] the intensity of symptoms on a numeric rating scale, 12,13 and Outcome Related to Impact on Daily Living (ORIDL, formerly referred to as GHHOS). 46 In retrospective outcome studies, your random sample of medical records will enable you to get an overview of documented outcomes and quality of documentation before planning in more detail.…”
Section: Gracementioning
confidence: 99%